Community Based Forest Management as a Tool for Sustainable Forest Management in Cross River State, Nigeria (2013)
Community-Based Forest Management (CBFM) in Cross River State (CRS) was investigated with a view to understanding its efficiency and effectiveness as a tool for sustainable forest management in the State. Four sets of questionnaire were administered to forestry officials; forest edge communities; timber dealers/saw millers: and relevant Non-Governmental Originations (NGOs).Three-stage sampling technique was adopted to sample six communities. The stages of sampling included: senatorial districts, Local Government Areas and communities. Data collected were analysed using descriptive statistics. The performance of CBFM was assessed against the ATO/ITTO’s Criteria and Indicators for the Sustainable Management of African Natural Tropica1 Forests. Results show that the average size of Community forests was between 101 and over 1000 ha per community. The level of awareness about community forest management was about 96% while 86% of the respondents participated in CBFM activities. The most significant gain of CBFM has been the meaningful partnership between the Cross River State Forestry Commission (CRSFC) and the forest edge communities in protecting and managing the forest resources. The existing benefit- sharing formula of CBFM proceeds is 1:4 in favour of government for government- established plantations, while communities have 7:3 of proceeds derived from community forests. The current sharing formula for the products obtained from reserved natural forests is 1:1. We suggest that a mutually acceptable formula should be worked out among the stakeholders. Some of the problems and challenges confronting the implementation of CBFM in the state include: inadequate encouragement and Cooperation among some members of the communities: inadequate incentives (seedlings, etc) and equipment (farm tools, etc); and capacity building; insufficient monitoring and evaluation by the relevant staff of the Forestry Commission. CBFM has done fairly well in certain aspects of sustainable forest management. However, aspects of maintenance of multiple functions of forests; creation of enabling environment; state economic and fiscal policies, policy to encourage forestry enterprises; effective monitoring and evaluation of forest management policy and adequate mechanisms for law enforcement have to be taken more seriously if CBFM v would serve as a veritable tool for sustainable forest management in Cross river State, Nigeria